Application of optimum digital filter based on genetic algorithms for transition edge sensor detector. (2015) - Shaaban, Noha
We propose a new signal processing method to improve the energy resolution of superconducting tunnel junction X-ray detectors. An optimum FIR (Finite Impulse Response) filter design tool based on fast Fourier transform was developed using genetic algorithms. The fast Fourier transform is perhaps one of the most used algorithms today in the analysis and manipulation of digital or discrete data. The main feature of this tool is that it needs a minimum number of parameters to specify the FIR filter specifications. This tool was applied successfully on transition edge sensor detector.